The Effect of 5A Success Preparation Program for Professional Nursing and Midwifery Licensing Examination on Adult and Gerontological Knowledge Scores and Satisfaction of Student nurse - Duangkaew, Jittima; Chatrung, Chutikarn; Chompuming, Wirongrong; Chantorn, Ausaniyaphon (NU Journal of Nursing and Health Sciences, 2023)
This quasi-experimental, one-group, pretest–posttest research aimed to compare the mean scores of pretest and posttest knowledge scores in adult and gerontological nursing subjects, and also to evaluate the satisfaction towards the Preparation Program 5A Success for comprehensive examination in adult and gerontological nursing subjects among Boromarajonani College of Nursing, Suphanburi. The sample group comprised 115 nursing students in the 4th year of Class 24th, Academic Year 2021 selected by purposive sampling. The 5A Success consisted of Self- management support of Glasgow. The Program consisted of five stages: 1) Assess 2) Advise 3) Agree 4) Assist and 5) Arrange. Content validity were revised by the experts. The data were collected with the Adult and Gerontological Nursing Subject Tests with KR-20 reliability at 0.74 and 0.78 and a satisfaction survey with Cronbach’ s alpha coefficient at 0.84. The demographic data were analyzed with descriptive statistics, comparing the pretest and posttest scores with paired t-tests and Wilcoxon Signed Rank Test. The results showed that: The posttest average scores of adult and gerontological nursing subjects were higher than the pretest average scores at the statistically significant (p<0.001). Satisfaction on the Preparation Program for Nursing comprehensive examination in both adult and gerontological nursing subjects received the highest score ( = 4.65, S.D. = 0.48). The 5A Success Preparation program could be implemented to develop a better comprehensive examination outcome and nursing board-licensed examination